Outpatient management of pulmonary embolism. Issue 155 (July 2017) - Roy, P.-M.; Moumneh, T.; Penaloza, A.; Sanchez, O.
Abstract: Despite clear potential benefits of outpatient care, most patients suffering from pulmonary embolism (PE) are currently hospitalized due to the fear of possible adverse events. Nevertheless, some teams have increased or envisage to increase outpatient treatment or early discharge. We performed a narrative systematic review of studies published on this topic. We identified three meta-analyses and 23 studies, which involved 3671 patients managed at home (n = 3036) or discharged early (n = 535). Two main different approaches were applied to select patients eligible for outpatient in recent prospective studies, one based on a list of pragmatic criteria as the HESTIA rule, the other adding severity criteria (i.e. risk of death) as the Pulmonary Embolism Severity Criteria (PESI) or simplified PESI. In all these studies, a specific follow-up was performed for patients managed at home involving a dedicated team. The overall early (i.e. between 1 to 3 months) complication rate was low, < 2% for thromboembolic recurrences or major bleedings and < 3% for deaths with no evidence in favour of one selection strategy or another. Outpatient management appears to be feasible and safe for many patients with PE. In the coming years, outpatient treatment may be considered as the first line management for hemodynamically stable PE patients, subject to the respect of simple eligibility criteria and on the condition that a specific procedure for outpatient care is developed in advance. Highlights: Selected patients with acute pulmonary embolism can be safely treated at home. Eligibility criteria are firstly pragmatic as those regrouped in the HESTIA rule. Severity criteria as a low PESI score are sometimes used in addition. A specific procedure for outpatient care of PE patients must be provided.